Defibrotide for the treatment of hepatic veno‐occlusive disease/sinusoidal obstruction syndrome following nontransplant‐associated chemotherapy: Final results from a post hoc analysis of data from an expanded‐access program. Issue 10 (6th June 2018) - Kernan, Nancy A.; Richardson, Paul G.; Smith, Angela R.; Triplett, Brandon M.; Antin, Joseph H.; Lehmann, Leslie; Messinger, Yoav; Liang, Wei; Hume, Robin; Tappe, William; Soiffer, Robert J.; Grupp, Stephan A.
Abstract: Background: Hepatic veno‐occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) is a potentially fatal complication of conditioning for hematopoietic stem cell transplantation (HSCT) but can occur after nontransplant‐associated chemotherapy. Following HSCT, VOD/SOS with multi‐organ dysfunction (MOD) may be associated with >80% mortality. Defibrotide is approved to treat severe hepatic VOD/SOS post‐HSCT in patients aged >1 month in the European Union and hepatic VOD/SOS with renal or pulmonary dysfunction post‐HSCT in the United States. Prior to US approval, defibrotide was available to treat VOD/SOS through an expanded‐access treatment (T‐IND) program. A post hoc analysis of nontransplant‐associated VOD/SOS patients treated with defibrotide initiated within 30 days of starting chemotherapy and followed for 70 days is presented. Procedure: Patients were diagnosed by Baltimore or modified Seattle criteria or biopsy, and received defibrotide 25 mg/kg/day in four divided doses (≥21 days recommended). Results: Of the 1, 154 patients in the T‐IND, 137 had nontransplant‐associated VOD/SOS, 82 of whom developed VOD/SOS within 30 days of starting chemotherapy. Of them, 66 (80.5%) were aged ≤16 years. Across all the 82 patients, Kaplan–Meier estimated day +70 survival was 74.1%, 65.8% in patients with MOD (n = 38), and 81.3% in patients without MOD (n = 44). By age group, Kaplan–Meier estimated day +70 survival was 80.1% in pediatric patients (n = 66) and 50.0% in adults (n = 16). Treatment‐related adverse events occurred in 26.8%. Conclusions: In this post hoc analysis of 82 patients initiating defibrotide within 30 days of starting chemotherapy, Kaplan–Meier estimated survival was 74.1% at 70 days after defibrotide initiation. Safety profile was consistent with prior defibrotide studies.